Internalization of Tawhid and Islamic Character in Schools/Madrasah - Rika Riauwati; Haris Riadi (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to examine the internalization of tawhid and Islamic character in schools/madrasah as an effort to form students who are faithful, noble in character, and capable of facing the challenges of the times. The method used is library research (library research) by analyzing various scientific sources in the form of relevant national and international journal articles in the last five years. The results of the study show that tawhid is the main foundation in Islamic education that not only functions as a theological concept, but also as a basis in the formation of Islamic character. The internalization of tawhid can be carried out through various strategies, such as curriculum integration, habituation of religious activities, teacher exemplary behavior, and the creation of an Islamic school culture. However, the process faces various challenges, especially in the modern era characterized by technological developments, social environmental influences, and limitations in the roles of teachers and families. Therefore, a comprehensive solution is needed through strengthening the role of teachers, synergy between schools and families, and the wise use of technology. This study affirms that the internalization of tawhid and Islamic character has a strategic role in shaping a generation that is faithful, knowledgeable, and noble in character, so that Islamic education needs to be continuously developed in an adaptive and contextual manner in accordance with the times.